Phenomenology Study: The Role of the Head Nurses in Maintaining Occupational Safety and Health Nurses - Yulis, Rahma; Novieastari, Enie; Rachmawati, Imami Nur; Nugraha, M Akbar (Jurnal Berita Ilmu Keperawatan, 2025)
The head nurse's role in maintaining the occupational health and safety of nurses. This research aimed to gain head nurses' experience in maintaining the safety and occupational health nurses. This study used a qualitative design with a phenomenological method in one of the type A referral hospitals in Jakarta. The number of participants in this study was 7 heads nurses from different rooms selected using the purposive sampling method with the maximum variation sampling type. The data collection process was carried out using in-depth interview techniques (50-60 minutes), field notes, and recording devices. Data analysis using the Colaizzi method. This research identified seven themes: 1) Concern for the condition of the human resources of nurses. 2) Enhance nurses' awareness of the importance of maintaining personal safety and health. 3) Give aid and special treatment to injured nurses. 4) Observe the accidents and illnesses  often occurring in the room. 5) Provide a conducive working atmosphere for the management, facilities, health care team, and work climate. 6) Minimize or eliminate the risk of danger and illness occurring. 7)  Reflection of head nurses on the efforts that have been made. Conclusion: the head nurses played an important role in preventing work accidents in nurses, because the head nurses is a nursing manager who interacts directly with nurses in the room. The head nurse can improve the role and function of the head of the of leadership and management of the Head nurses, improving knowledge about occupational safety and health management, and leadership ability